Axon-glia interaction and membrane traffic in myelin formation - White, Robin; Krämer-Albers, Eva-Maria (Frontiers in Cellular Neuroscience, 2014)
In vertebrate nervous systems myelination of neuronal axons has evolved to increase conduction velocity of electrical impulses with minimal space and energy requirements. Myelin is formed by specialized glial cells which ensheath axons with a lipid-rich insulating membrane. Myelination is a multi-step process initiated by axon-glia recognition triggering glial polarization followed by targeted myelin membrane expansion and compaction. Thereby, a myelin sheath of complex subdomain structure is established. Continuous communication between neurons and glial cells is essential for myelin maintenance and axonal integrity. A diverse group of diseases, from multiple sclerosis to schizophrenia, have been linked to malfunction of myelinating cells reflecting the physiological importance of the axon-glial unit. This review describes the mechanisms of axonal signal integration by oligodendrocytes emphasizing the central role of the Src-family kinase Fyn during central nervous system (CNS) myelination. Furthermore, we discuss myelin membrane trafficking with particular focus on endocytic recycling and the control of proteolipid protein (PLP) transport by soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins. Finally, PLP mistrafficking is considered in the context of myelin diseases.